Design and additive manufacturing of novel conformal cooling molds. (November 2020) - Tan, Chaolin; Wang, Di; Ma, Wenyou; Chen, Yaorong; Chen, Shijin; Yang, Yongqiang; Zhou, Kesong
Abstract: Additive manufacturing (AM) offers high-freedom in the design and processing of components with complex internal structures. In this work, a new injection mold with the self-supporting large cooling channel and tailored porous structures was designed to improve cooling efficiency and save AM build costs. The optimized internal supports suppressed the collapse and warpage of large channels, which improves the manufacturability and breaks the geometric constraints of laser powder bed fusion (LPBF). The formable diameter of self-supporting channels is significantly increased (≥20 mm). In comparison to the 8 mm normal-sized channel, the self-supporting 13 mm channel reduces the cooling time of more than 20%. Additionally, the porous diamond structure was designated in the assembly part of the mold to save the materials and build time. To tune the strength, a core-shell composite structure with solid shell surrounding inner porous structures is designed. The influence of the wall thickness on the mechanical property of the composite structure was explored, which guides the specific mold design. Finally, a mold with the above-mentioned novel design was successfully processed by LPBF, which substantiates the manufacturability of innovative design. This work also inspires other industrial applications of AM-processed components with improved performance and functionality. Graphical abstract: Unlabelled Image Highlights: Internal supports breaks the manufacturing constraints in LPBF large channel. Self-supporting large cooling channels of mold increase cooling efficiency. Tailored porous structures in the mold save build time and material costs. A mold product with innovative design was produced by LPBF successfully.